Political influence, corporate governance and financial reporting quality : evidence from companies in Malaysia : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accountancy at Massey University, Wellington, New Zealand - Md Salleh, Mohd Fairuz Bin (Massey University, 2009)
This study investigates the relationship between political influence, corporate governance and financial reporting quality using Malaysian data spanning 1999-2003. The study builds upon agency theory, analysing the conflicting incentives of politicians, shareholders and managers, and how they affect governance and financial reporting. Four hypotheses are put forward: (1) Political influence is associated with lower financial reporting quality; (2) Political influence is associated with weaker corporate governance; (3) After controlling for political influence, weak corporate governance is associated with low financial reporting quality; and (4) Corporate governance mediates the relationship between political influence and financial reporting quality. In addition, knowledge obtained from interviews of top managers from several companies is used to look further at the influence of politics in managerial decision-making, particularly in relation to governance structure, accounting and reporting. Malaysia offers an interesting and important case study of relationship-based capitalism. Malaysian companies are regarded as politically sensitive, they are highly concentrated, and government participation in equity ownership is significant. One advance is that this study uses three observable proxies for political influence: government ownership, the presence of politician/s on the board, and the existence of a golden share giving special rights to the government. It appears that political influence is not a single construct. The findings support previous studies only if political influence is defined as the presence of politician/s on the board. Government ownership improves both governance and reporting quality, contrary to the findings of most previous studies. Having a golden share is not associated with governance or financial reporting quality. These findings suggest that institutional details matter when considering the effect of political influence on corporate governance and financial reporting. Findings from interviews provide a rich source of support for some of the quantitative findings, and new details on the complexity of the relationship between governments, boards and managers. Overall, the study provides insights and additional guidance for regulators and policy makers, for improving the design of corporate governance features and financial reporting frameworks as well as for deciding on the level of involvement of government and politicians in business The contrasts with findings of earlier studies in Western economies suggest opportunities for future research to understand the sources of the differences.
Keywords: Corporate governance, Malaysia; Financial statements, Malaysia; Malaysia; Political influence